Maritime safety in the approach of L. von Bertalanffy's general system theory - Zięcina Marcin; Sokołowski Wojciech; Ficoń Krzysztof (2022)
The paper presents an original concept of maritime safety modeling using the tool apparatus of L. von Bertalanffy's general systems theory. In the introduction, the methodological assumptions of the general systems theory were formulated, which was used to build a formalized model of the maritime security system, including all the basic structures of the system topology, i.e. separated components, basic relations between these elements and the specification of the system environment. Using the tool apparatus of the general systems theory by L. von Bertalanffy in the modeled Maritime Security System, the basic elements of the system approach were distinguished, i.e. the concept of a set, structural elements, system relations, external environment and system inputs and outputs. The main research thesis is that maritime security, which is a kind of open system, can be interpreted on the basis of general systems theory, which provides effective research tools for a broader look at the application side of maritime safety. The basis of this thesis is the assumption that maritime security can be interpreted as a praxeological system of action that functions in a specific holistic environment, constantly exchanging information, energy and matter with it, thanks to which the entropy (disorder) of the system remains in a certain (safe) equilibrium. Finally, a brief analysis of the controversy surrounding a universal systems approach with regard to application in the social sciences and humanities was conducted.